Investigation of the structure of CaO-Al2O3-SiO2 melts as a basis for the development of new agglomerated welding fluxes and industrial refractories - Sokol’skii V.E.; Pruttskov D.V.; Busko V.M.; Kazimirov V.P.; Roik O.S.; Chyrkin A.D.; Galinich V.I.; Goncharov I.A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A significant number of welding fluxes and industrial ceramics are produced in the Ukraine. The production of these materials is sufficient for both domestic needs and significant export. It is assumed that the ternary CaO-Al2O3-SiO2 system may become the basis for the development of agglomerated welding fluxes and technical ceramics. Three samples of ternary CaO-Al2O3-SiO2 system were studied by means of high-temperature X-ray diffraction above the melting point: 23.3CaO- 14.7Al2O3-62.0SiO2 wt. % (sample 1, eutectic), 9.8CaO-19.8Al2O3-70.4SiO2 wt. % (sample 2, eutectic), 15.6 CaO- 36.5Al2O3-47.9SiO2 wt. % (sample 3). Experimental scattering intensity curves, structure factors and the radial distribution function of atoms were obtained. The structural parameters of short-range order were calculated using melt structure models obtained by Reverse Monte Carlo method. The existence of microparticle associates of the mullite or sillimanite type immersed in the slag matrix is assumed. It is assumed that the calcium ions coordinated aroundthese associates are surrounded by oxygen melt anions. Such a structure can be considered as a colloidal solution. The microparticle of mullite is the core of the aggregate that is surrounded by calcium and oxygen ions from the molten medium.